Profile of ocular trauma in the Solomon Islands. (19th December 2013) - Baker, Michelle L; Painter, Geoffrey; Hewitt, Alex W; Amirul Islam, F M; Szetu, John; Qalo, Mundi; Keeffe, Jill
Abstract Background The objective of this study was to characterize the causes of ocular trauma and determine the risk factors for infection and vision loss following ocular trauma in the Solomon Islands. Design A prospective clinic‐based study. Participants A total of 507 patients with ocular trauma who were reviewed at the National Referral Hospital in Honiara or one of five provincial eye clinics were included. Methods An interview‐based questionnaire to determine the circumstances of ocular trauma, and an ocular examination to elicit the trauma sustained, infectious sequelae and the visual outcome. Main Outcome Measure Visual acuity. Results Males were significantly more likely to have ocular trauma than females (P = 0.01). The major cause of ocular trauma in young boys and girls was being poked by a stick, followed by lime burns in young boys. For both genders, physical violence resulted in most injuries across all adult age groups. Microbial keratitis complicated 4.4% of ocular trauma. Monocular vision impairment (<6/18) occurred in 5.5% of participants and was more likely to occur if female (P = 0.02). Conclusions Ocular trauma is a significant cause of visual morbidity in the Solomon Islands. The results from this prospective study provide a basis for planning blindness prevention programmes in the Western Pacific.